Magnetically driven microrobots: Recent progress and future development. (March 2023) - Shen, Honglin; Cai, Shuxiang; Wang, Zhen; Ge, Zhixing; Yang, Wenguang
Graphical abstract: Highlights: Construction and driving method of magnetic field and materials and shapes of magnetically driven microrobots are reviewed. Manufacturing method and applications of magnetically driven microrobot are reviewed. The challenges and future directions of magnetically driven microrobot for biomedical applications are summarized. Abstract: Microrobots have received extensive attention in the past few decades, and the in-depth research of micro-nano processing technology and micro-nano materials has promoted the further development of microrobots. Researchers have successfully achieved the use of chemical fuels, and electric, sound, and magnetic fields to promote the movement of microrobots. Among many power sources, magnetic fields have attracted wide attention because of their advantages including remote wireless operation and harmlessness to the human body. After decades of development, magnetically driven microrobots have been extensively studied in the fields of cargo transportation, cell manipulation, toxic substance removal, and micromanipulation. This article first summarizes the driving methods of magnetically driven microrobots in recent years, then summarizes the materials for manufacturing microrobots, and summarizes the shapes of typical microrobots, including spiral, spherical, and linear structures. After that, the processing methods are sorted out, and the application of magnetic-driven microrobots in biomedicine and other fields in recent years is summarized. Finally, the development prospects of magnetic-driven microrobots are discussed.